Owning up : poverty, assets, and the American dream - Miller-Adams, Michelle, 1959- (Brookings Institution Press, 2002)
This text is about assets and the difference they can make in the lives of the poor. It expands the concept of asset building to encompass a range of skills and support systems that are necessary to lift people out of poverty. It identifies four types of asset: economic, human, social and natural.